Antagonistic effects of Satureja hortensis essential oil against AFB₁ on human lymphocytes in vitro - Ceker, S.; Agar, G.; Alpsoy, L.; Nardemir, G.; Kizil, H.E. (Цитология и генетика, 2014)
Satureja hortensis L. (Lamiaceae) используется как народное средство для лечения разных заболеваний, таких как спазмы, мышечные боли, тошнота, нарушения пищеварения, диарея и инфекционные заболевания. В настоящей работе на примере лимфоцитов человека in vitro изучали антагонистическое действие эфирного масла S. hortensis (SHE) на афлатоксины B₁ (AFB₁). Анализ эфирных масел проводился с помощью газовой хроматографии – масс-спектрометрии (GC-MS). Антигенотоксический эффект SHE был оценен на основании изучения обмена сестринских хроматид (SCE) и микроядерного теста против AFB₁. Кроме того, для оценки антиоксидативных эффектов SHE использовали уровень активностей малоновых диальдегидов (MDA), супероксиддисмутазы (SOD) и глютатионпероксидазы (GPx). Показано, что AFB₁ (5 µM) увеличивает частоту SCE, MN и уровень MDA. AFB₁ в той же концентрации снижает активность SOD и GPx. Однако различные концентрации SHE с AFB₁ снижали частоту SCE, MN и уровень MDA, а также существенно увеличивали активность SOD и GPx. Концентрации SHE 1.0, 1.5, 2.0 µL были наиболее эффективными. Результаты работы четко показали, что SHE имеет сильный антиоксидативный и анти-генотоксический эффект. Такая биологическая активность определяется химическим составом SHE. Satureja hortensis L. (Lamiaceae) has been used as a folk remedy to treat various such as cramps, muscle pains, nausea, indigestion, diarrhea, and infectious diseases. In this study, the antagonistic effects of essential oil of S. hortensis (SHE) were studied against aflatoxin B₁ (AFB₁) in human lymphocytes in vitro. The analysis of the essential oil was performed by using Gas chromatography-mass spectrometry (GC-MS). Anti-genotoxic effects of the SHEs was evaluated using sister chromatid exchange (SCE), micronuclei (MN) tests against AFB₁. Also level of malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities used to determine the anti-oxidative effects of the SHEs. This result showed AFB₁ (5 μM) increased the frequencies of SCE, MN and the level of MDA. AFB₁ at the same concentration decreased the activities of SOD and GPx. However, different concentrations of SHE with AFB₁ decreased the frequency of SCE and MN and level of MDA and also increased the activities of SOD and GPx significantly. Especially, the 1.0, 1.5, 2.0 μL dose of SHE are more effective than other doses. The results of this experiment have clearly shown that SHE has strong antioxidative and antigenotoxic effects, these biological activities of SHEs can be due to its component.